2013
DOI: 10.1186/1471-244x-13-125
|View full text |Cite
|
Sign up to set email alerts
|

Reduced P300 amplitude during retrieval on a spatial working memory task in a community sample of adolescents who report psychotic symptoms

Abstract: BackgroundDeficits in working memory are widely reported in schizophrenia and are considered a trait marker for the disorder. Event-related potentials (ERPs) and imaging data suggest that these differences in working memory performance may be due to aberrant functioning in the prefrontal and parietal cortices. Research suggests that many of the same risk factors for schizophrenia are shared with individuals from the general population who report psychotic symptoms.MethodsForty-two participants (age range 11–13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 63 publications
(75 reference statements)
0
4
1
Order By: Relevance
“…Results indicate that event-related time-domain responses were smaller in SZ than in HC, supporting Hypothesis 1. Contrary to predictions for event-related responses (e.g., Rawdon et al, 2013) but consistent with overt performance, abnormal timelocked neural activity to WM item presentation did not vary with WM load.…”
Section: Time-domain Phenomenacontrasting
confidence: 97%
See 2 more Smart Citations
“…Results indicate that event-related time-domain responses were smaller in SZ than in HC, supporting Hypothesis 1. Contrary to predictions for event-related responses (e.g., Rawdon et al, 2013) but consistent with overt performance, abnormal timelocked neural activity to WM item presentation did not vary with WM load.…”
Section: Time-domain Phenomenacontrasting
confidence: 97%
“…fMRI studies have reported less activity in SZ than in healthy controls (HC) in brain regions associated with WM encoding and retention, including dorsolateral prefrontal cortex (DLPFC), anterior cingulate cortex (ACC), superior temporal cortex, and posterior cortex (e.g., Cannon et al, ; Eich, Nee, Insel, Malapani, & Smith, ; Glahn et al, ; Karlsgodt et al, ; Unschuld et al, ; Van Snellenberg et al, ; Wible et al, ). Electromagnetic (EEG, MEG) neuroimaging has reported smaller ERP amplitude and event‐related desynchronization in SZ than in HC related to WM encoding and retention (Berger et al, ; Hsieh & Ranganath, ; Johannessen, Bi, Jiang, Kenney, & Chen, ; Light et al, ; Raghavachar et al, ; Rawdon et al, ; Roux, Wibral, Mohr, Singer, & Uhlhaas, ; Sauseng et al, ; Stephane et al, ; Zanto, Rubens, Thangavel, & Gazzaley, ). Lower power in gamma‐band responses has been interpreted as an indication of less efficient item encoding, whereas lower power in theta‐band responses has been considered a sign of less efficient item retention in SZ.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the anatomical and physiological levels, adolescents who report PLEs, compared to those who do not report these, show structural (Satterthwaite et al 2016) and functional brain abnormalities (Wolf et al 2015), functional disconnectivity (Satterthwaite et al 2015), and a reduced amplitude of the P300 (event-related potentials) (Rawdon et al 2013) similar to those found in patients with psychosis.…”
Section: Psychotic-like Experiences: a Translational Approachmentioning
confidence: 95%
“…The P300 usually reflects stimulus evaluation and category, as well as updating of working memory (WM). P300 amplitudes correlate negatively with WM function, whereas P300 latencies correlate positively (see Christopher, Adam, & Robert, 2006; Polich, 2007; Rawdon et al, 2013; Steiner, Barry, & Gonsalvez, 2013). Because AP musicians presumably possess an internally fixed and long-term tonal template in which tone names are attached to given frequencies, they are able to name tones without references (Hirose et al, 2002; Levitin & Rogers, 2005; Siegel, 1974; Takeuchi & Hulse, 1993).…”
Section: Functional Correlates Of Apmentioning
confidence: 99%